TO EVALUATE THE ROLE OF CT KUB (KIDNEY, URETER, BLADDER) IN THE DETECTION OF UROLITHIASIS IN PATIENTS WITH ACUTE FLANK’S PAIN. - Abdul Wadood1 , Ayesha Malik2 , Abdul Salam3 , Khubroo Ali4 , Muhammad Usman5, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT: BACKGROUND: Urolithiasis is the most common urinary tract disease and acute flank’s pain is one of the most common symptoms of it. Urolithiasis affects both gender of all age groups but most common affected category was found to be the male. Computed Tomography is a gold standard modality and has great role for urolithiasis detection during KUB (Kidney, Ureter, Bladder) scan. The objectives of this study were to evaluate the role of Computed Tomography KUB (Kidney, Ureter, Bladder) in the detection of Urolithiasis in patients with acute flank’s pain and to identify the presence of renal tract calculi in KUB (Kidney, Ureter, Bladder) to confirm that which part is more affected due to calculus presences. METHOD: A cross sectional study with consecutive sampling was carried out at Department of Radiology, Medical Teaching Institute Hayatabad Medical Complex Peshawar, Pakistan from October 2022 to March 2023. 150 patients aged between 20-60 years presenting with acute flank’s pain were included in the study. Ethical approval was obtained. CT KUB of the patient was performed with 128 slices GE Computed Tomography (CT) scan machine on full urinary bladder in supine position 1 cm above the liver through symphysis pubis, used scan parameters technique 120 kV/Auto mA, 0.5 rotation with Standard Algorithm, 4 mm slice thickness and was taken field of view (FOV) according to the patient size. Axial, coronal and sagittal images are taken and soft-tissue window with 2 mm coronal and sagittal was also reconstructed. RESULTS: In total 150 patients presenting with acute flank’s pain, 273 stones were detected during CT KUB. The highest number of patients referred by Urologist (60.7%) followed by ER Physician (39.3%). Stones lie in renal calyx (32.7%), renal pelvis (36.7%) and ureter (30.7%). The presence of stones is higher in right kidney (51.4%) as compare to left kidney (38.6%) whereas in right ureter found more stones (17.9%) as compare to left ureter (14.7%). Obstructive Nephrolithiasis was reported to be (27.3%) and non-obstructive (72.7%). According to stone size, majority belongs to 6-10 mm (36.7%). The range of mean attenuation value (HU) was from 301-600 HU having (42.2%) and in most cases single stone were reported (51.3%). Hydronephrosis (65.3%) were the most common secondary signs of obstruction followed by Hydroureter (26.7%) and Perinephric stranding (23.4%). CONCLUSION: Computed Tomography KUB (Kidney, Ureter, Bladder) has main role and is key for detection and diagnosis of Urolithiasis. It helps to provide detail information for further treatment plans.